The financial crisis, labor market transitions and earnings: A gendered panel data analysis for Serbia - Niels-Hugo Blunch; Victor Sulla (Institute for the Study of Labor (IZA), 2011)
While results are starting to emerge, not much is known yet about the dynamics of the labor markets of the former Eastern economies, especially in the context of the current Financial Crisis. Arguably, this is mainly due to paucity of (panel) data. By examining labor market transitions, earnings levels, and earnings growth and their correlates using a recent panel data set for Serbia, this paper combines both of these issues. Estimation of gross transition probabilities reveals that females are disadvantaged in the Serbian labor market in terms of moving out of the two undesirable states, unemployment and economic inactivity, relative to males during the first year of the financial crisis - though males are harder hit than females in terms of the levels of unemployment. In terms of earnings, the picture is reversed, with females being worse off in terms of the levels of earnings, while they have experienced somewhat smaller earnings decreases than males (though, owing to the gender earnings gap, from a much lower base). Multinomial logit estimations of employment, unemployment, and inactivity transitions and OLS regressions of earnings and earnings growth reveal substantial gender differences related to individual, job, and firm characteristics. The overall results therefore hint at both males and females being hit in terms of employment and earnings, though in different ways. Finally, the paper discusses policy implications and provides suggestions for further research.
urn:nbn:de:101:1-2012010913711
Keywords: I31; J2; J24; J6; 330; financial crisis; gender; labor market flows; transition probabilities; earnings growth; panel data; Serbia; Lohndifferenzierung; Finanzmarktkrise; Arbeitsmarkt; Übergangswirtschaft; Einkommen; Panel; Schätzung; Serbien